Physiological markers of traffic-related stress during active travel. (January 2022) - Bigazzi, Alexander; Ausri, Fajar; Peddie, Luke; Fitch, Dillon; Puterman, Eli
Highlights: Early studies of active traveller stress markers report inconsistent findings. We propose a comprehensive conceptual framework of active traveller stress. No stress marker has yet been shown to be reliable for on-road active travellers. Key confounders include exertion, speed, weather, and subject-level modifiers. Recommendations include controlled experiments and more precise study framing. Abstract: Understanding perceptions of safety and comfort (PSC) while walking or cycling is essential to accommodating and encouraging active travel, but current measures of PSC, primarily surveys, suffer from validity and reliability issues. Physiological markers of stress like electrodermal activity and heart rate variability have been proposed as alternative, objective measures of PSC. This paper presents a literature summary and conceptual framework examining the use of physiological stress markers during walking and cycling. The existing studies of active traveller stress markers report inconsistent findings and account for limited controls. We propose a comprehensive conceptual framework to describe the array of dynamic stimuli experienced during active travel, with complex appraisals and multidimensional stress responses that feedback to travel behaviour and stimuli exposure, and culminate in a set of physiological outcomes triggered by activation of the autonomic nervous system – all moderated by numerous personal and trip-related factors. The key challenge of inferring traffic-related fear or discomfort from physiological markers measured on-road is potential confounding effects of: (1) non-traffic factors that induce or modify stress responses, (2) traffic factors that induce stress responses not associated with safety or comfort, and (3) personal and environmental factors that directly influence physiological measurements outside of a stress response. No physiological stress marker has yet been shown to be reliable for on-road active travellers, particularly not for inter-subject comparisons. Physiological markers have the potential to provide high-resolution, objective information about pedestrian and cyclist PSC, but further research, particularly controlled experiments, and more precise study framing are needed to ensure validity and address moderating and confounding factors.